Quantification of the collagen fibers of healthy and neoplastic mammary tissue in cats by the picrossirius red histochemical method - Jorge, Mariana Fernandes [UNESP]; Patrocínio, Ana Cláudia; Hataka, Alessandre [UNESP]; Sequeira, Júlio Lopes [UNESP] (Brazilian Journal of Veterinary Pathology, 2021)
Although feline mammary carcinoma is not the most prevalent among the species, its aggressive behavior represents a low life expectancy, compared with most undifferentiated types of breast cancer. Tissue stiffness induced by the accumulation of collagen fibers is related to a risk factor for carcinogenesis in healthy women and aggressiveness in those with breast cancer, which can also occur in cats. The objective of this work is to identify the relationship between stromal collagen density and aggressiveness of mammary carcinoma in cats, according to the peripheral and central tissue distribution by the Picrossirius Red histochemical method. Image.J® and MatLab® software were used for digital image processing. The mean values of kurtosis and entropy attributes were grouped into a control group, and low and high-grade carcinoma groups, analyzed with one-way ANOVA and Bonferroni’s multiple comparison test (p <0.01). Interpretation of stromal dynamics is important to evaluate both central and peripheral locations. According to entropy, there was a significant increase in the peripheral density in the carcinoma groups in relation to the control group, which can be justified by blood support. The same can be said of the central region, with a significant gain in collagen fibers from the tumors, indicated by kurtosis. The results suggest the presence of increases in stromal density in mammary carcinomas of cats, regardless of their graduation, and occurring in both regions.
Keywords: Breast cancer; Breast density; Carcinoma; Extracellular matrix; Feline